2003
DOI: 10.1128/jcm.41.5.2015-2026.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycobacterium avium subsp. paratuberculosis : Evidence for Limited Strain Diversity, Strain Sharing, and Identification of Unique Targets for Diagnosis

Abstract: The objectives of this study were to understand the molecular diversity of animal and human strains of Mycobacterium avium subsp. paratuberculosis isolated in the United States and to identify M. avium subsp. paratuberculosis-specific diagnostic molecular markers to aid in disease detection, prevention, and control. Multiplex PCR of IS900 integration loci (MPIL) and amplified fragment length polymorphism (AFLP) analyses were used to fingerprint M. avium subsp. paratuberculosis isolates recovered from animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 50 publications
6
90
0
Order By: Relevance
“…Until 2000, the majority of experimental studies in sheep did not use characterized ovine MAP strains, in contrast to later studies which have used tissue homogenates or low passage ovine MAP strains grown in vitro (Gwozdz et al, 2000a,b;Stewart et al, 2004;. The most common MAP isolates from clinical JD in sheep belong to the ovine genotype (Motiwala et al, 2004;Sevilla et al, 2005;Sevilla et al, 2007). Marked genetic diversity was detected among ovine isolates, as well as between ovine and both bovine and goat isolates (Motiwala et al, 2004).…”
Section: Long-term Ovine Map Challenge Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Until 2000, the majority of experimental studies in sheep did not use characterized ovine MAP strains, in contrast to later studies which have used tissue homogenates or low passage ovine MAP strains grown in vitro (Gwozdz et al, 2000a,b;Stewart et al, 2004;. The most common MAP isolates from clinical JD in sheep belong to the ovine genotype (Motiwala et al, 2004;Sevilla et al, 2005;Sevilla et al, 2007). Marked genetic diversity was detected among ovine isolates, as well as between ovine and both bovine and goat isolates (Motiwala et al, 2004).…”
Section: Long-term Ovine Map Challenge Modelmentioning
confidence: 99%
“…Twenty-six to 50% of isolates from clinical cases in goats have been of bovine genotypes (Motiwala et al, 2004;Sevilla et al, 2005;Sevilla et al, 2007). Motiwala et al (2004) detected little genetic diversity between and within bovine and goat isolates, but Sevilla et al (2007) showed that goat isolates had a high degree of genetic heterogeneity.…”
Section: Long-term Caprine Map Challenge Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies were based on existing isolate collections, and showed a fair amount of homogeneity within M. paratuberculosis strains and revealed that M. paratuberculosis strains from human infections were less diverse compared to cattle (Wynne et al, 2011). Results were derived from several methods making it difficult to make direct comparisons, including IS1311 restriction fragment length polymorphism (RFLP) analyses (Whittington et al, 2000;Motiwala et al, 2003;Singh et al, 2010b;Okuni et al, 2012;Liapi et al, 2015), (Stevenson et al, 2009;Fernandez-Silva et al, 2012) randomly amplified polymorphic DNA (RAPD) (Pillai et al, 2001), multi-locus short sequence repeat sequencing (MLSSR) (Fernandez-Silva et al, 2012), Multiplex PCR of IS900 integration loci (MPIL) (Motiwala et al, 2004), short sequence repeats (SSR) (Ghadiali et al, 2004), and single nucleotide polymorphisms (SNPs) (Wynne et al, 2011). A tally of the type of M. paratuberculosis (e.g.…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
“…Methods for differentiation or subtyping of MAP, such as IS900 multiplex PCR (Bull et al, 2000), RFLP -random fragment length polymorphism (Pavlik et al, 1999), AFLP -amplified fragment length polymorphism (Motiwala et al, 2003) or MLSSR -multilocus short sequence repeat (Amonsin et al, 2004) have been previously developed. RFLP analysis of the examined tissue isolates identified RFLP type B-C1 in all cases.…”
Section: Map In Various Tissuesmentioning
confidence: 99%